Learning Environments and Environmental Learning in Schools: An Analysis of Published Papers in India: A Review of Learning Environments and Environmental Learning in Indian Schools (Journal of Advances and Scholarly Researches in Allied Education, 2019)
With progressively more research being conducted internationally on the efficacy of learning from the environment both inside and outside the traditional classroom, and environmental education for a sustainable future this paper attempts to review research and studies of both the aspects published in India since 2005. This research paper is an analytical review of the literature related to the variable Learning Environment in schools of India and the induction of environmental education. The researcher has selected the present topic “Learning from the environment Analysis of published papers in India” for analytical study based on her own research work titled as “Impact of Active and Outdoor Learning Environment on Student Engagement, Attitude and Learning Outcome - A Study conducted in Kotdwara, Uttarakhand” being pursued for the degree of Doctor of Philosophy.